2016
DOI: 10.5194/tc-10-811-2016
|View full text |Cite
|
Sign up to set email alerts
|

Constraining variable density of ice shelves using wide-angle radar measurements

Abstract: Abstract. The thickness of ice shelves, a basic parameter for mass balance estimates, is typically inferred using hydrostatic equilibrium, for which knowledge of the depthaveraged density is essential. The densification from snow to ice depends on a number of local factors (e.g., temperature and surface mass balance) causing spatial and temporal variations in density-depth profiles. However, direct measurements of firn density are sparse, requiring substantial logistical effort. Here, we infer density from rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…4). Almost all ice shelf channels at RBIS are connected to the grounding line and may arise from water-filled subglacial conduits injecting subglacial melt water into the ice shelf cavity, driving a spatially localized buoyant melt water plume (Jenkins, 2011;Le Brocq et al, 2013;Drews et al, 2017;Sergienko, 2013). Such localized melting near the grounding zone has been previously observed on Pine Island Ice Shelf using similar methods as done here (Dutrieux et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…4). Almost all ice shelf channels at RBIS are connected to the grounding line and may arise from water-filled subglacial conduits injecting subglacial melt water into the ice shelf cavity, driving a spatially localized buoyant melt water plume (Jenkins, 2011;Le Brocq et al, 2013;Drews et al, 2017;Sergienko, 2013). Such localized melting near the grounding zone has been previously observed on Pine Island Ice Shelf using similar methods as done here (Dutrieux et al, 2013).…”
Section: Discussionsupporting
confidence: 61%
“…Consequently, we do not capture their spatial (and temporal) variations on the length scales associated with ice shelf channels. Both Drews et al (2016) and Langley et al (2014) found evidence in the shallow radar stratigraphy that the SMB may be locally elevated in those areas, potentially reflecting the deposition of drifting snow at the bottom of surface slopes (Frezzotti et al, 2007). If this holds true, then the systematic underestimation of the SMB would result in a positive bias of the LBMB in those areas.…”
Section: Surface Mass Balancementioning
confidence: 99%
“…The impact of the firn air content misestimation on the derivation of the hydrostatic ice thickness is further discussed in Lenaerts et al (2017). Moreover, Drews et al (2016) used wide-angle radar measurements in conjunction with ice coring and found that firn density varies spatially over tens of kilometres scales, in particular across ice shelf channels, where surface melt water collects in the corresponding surface depressions and locally refreezes. Therefore, we anticipate that at least some of the variability seen in the LBMB field is due to unresolved variations in firn density.…”
Section: Hydrostatic Inversionmentioning
confidence: 99%
“…The largest and most ill-constrained error source presumably lies in the NMO correction, which presupposes horizontal IRHs and oblique (but straight) raypaths. In Antarctica, dips of IRHs are typically small and even if the density varies strongly with depth, effects of ray bending are equally small (Barrett and others, 2007;Drews and others, 2016). However, the positions of the sleds carrying both receiver and transmitters were not well defined: depending on the surface slope, the towing rope was not always fully tensioned and sleds also drifted into an off-axis position compared with the heading of the snowmobile.…”
Section: Radar Data Acquisition and Processingmentioning
confidence: 99%